Gender Sensitivity of the Serbian Parliament – mapping the power of the women MPs - Vukomanović, Dijana (Sociološki pregled, 2021)
Mapping the power of women MPs in the Serbian Parliament, through the analysis of the membership and the leadership of the Parliament and parliamentary committees, indicates that women MPs dominate the socio-cultural cluster of the committees, as well as foreign affairs and European integration committees. Women MPs are increasingly ore visible in legislative-judiciary committees, while interior, defence and security affairs committees and minimally open to their membership. There is a growing trend of engaging women MPs in committees for ecology, then in trade and finance and, to a lesser extent, in infrastructure. Institutional gender sensitivity of the Serbian Parliament is still inadequate, and changes to the Rules of Procedure and the Code of Conduct are necessary in order to introduce gender-sensitive rules and procedures.
Keywords: women MPs; election quotas; gender sensitivity of the parliament; parliamentary committees